Analysis for reliability and validity of gross motor function and health fitness tests for children with developmental disabilities - Yoon, Tae-Hyun; Mun, You-Kyung; Lee, Jong-Sun; Min, Su-Kyung; Jee, Yong-Seok (Journal of exercise rehabilitation, 2019)
The aim of this study was to determine the reliability and validity of gross motor function and health fitness assessment tests for children with developmental disabilities. All 35 participants who took part in this study on a voluntary basis were male children (age, 10.31±1.25 years). All selected tests for gross motor function and health fitness assess-ments were used in previous studies to measure basic physical health and motor abilities, which include strength (grip strength test), muscular endurance (modified sit-ups test), flexibility (sit and reach test), and car-diopulmonary endurance (15-m shuttle run test). Reliability was ana-lyzed using intraclass correlation coefficients in the pretest-posttest and Bland-Altman graphs study. Pearson correlation was used to ana-lyze convergent validity and analysis of variance was used to analyze variations among age groups. Lastly, a correlation analysis was con-ducted between the tests in gross motor function and health fitness as-sessments. This study indicates that gross motor function and health fitness assessments have obtained adequate reliability parameters and are able to determine differences in children from 9 to 12 years of age. The tests performed were simple to use, safe, and suitable for children with developmental disabilities.